THE IMPACT OF OIL PRICES ON THE PUBLIC BUDGET AND TRADE BALANCE IN IRAQ FOR THE DURATION (2004-2017) - زيارة رحيم حسوني; دعدوش علي عبد الكاظم (Journal of Economics and Administrative Sciences, 2019)
The fluctuations in oil prices in world markets affect the general budget and the trade balance of the rent countries, because oil is a strategic commodity affected by economic and political factors. The fluctuations in oil prices affect the public budgets of the rent countries through the public revenue side of oil revenues. On the other hand, these fluctuations affect the balance of trade through the volume of oil exports, which lead to imbalance of trade surplus or deficit . And that the revenues of the general budget in Iraq depends on (88% - 90%) on oil revenues as the changes in global oil prices have a significant impact on the reality of the Iraqi economy unilaterally, as well as the Iraqi trade balance, which depends on a single commodity (crude oil) In the volume of total exports, and fluctuations in oil prices (rise and fall) will lead to imbalance in the volume of foreign trade, causing the country economic exposure and dependence on international markets, and this is a challenge and concern for economic policy in the country, It is a promise Development will deepen imbalances in the Iraqi economy ,and thus not for economic diversification of the country .